Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Matematika di Kelas XI MIPA 3 SMA Negeri 3 Samarinda - Margareta Nuri Ardiantari (SISTEMA: Jurnal Pendidikan, 2022)
Mathematics is one of the most essential subjects in high school (SMA). With the low level of student's understanding of Mathematics in class XI MIPA 3 SMA Negeri 3 Samarinda, researchers consider it necessary to conduct research to improve learning. Learning improvement is carried out through classroom action research (CAR) with 2 cycles, each consisting of 3 meetings. The learning activities were carried out at SMA Negeri 3 Samarinda Class XI MIPA 3, totalling 36 students, consisting of 11 students. This classroom action research was conducted with the aim of improving student learning outcomes in even-semester Mathematics subjects, especially on Tangent Lines and Polynomials by applying the Discovery Learning learning model. After improving learning, student learning outcomes showed an increase. This is shown from the data collected, from data processing obtained 10 students (27.78%) completed learning with an average score of 54.17 in the pre-cycle, to 28 students (77.78%) completed learning with a grade of an average of 74.03 in the first cycle, and 35 students (97.22%) completed their studies with an average score of 80.83 in the second cycle. That is, from the pre-cycle to the first cycle of students who finished studying increased by 18 students and from the first cycle to the second cycle of students who completed learning increased by 7 students. Students complete learning in the sense of getting a value of 70, this 70 is the Minimum Completeness Criteria (KKM). From the data obtained and calculations, it can be concluded that: "The application of the Discovery Learning Learning Model can improve learning outcomes for Even Semester Mathematics Students in class XI MIPA 3 SMA Negeri 3 Samarinda in the academic year 2021 - 2022. Keywords: Discovery Learning, Learning Outcomes, Mathematics